Higher Education Dynamic Archives Management (A Case Study of Universitas PGRI Palembang) - Lian, Bukman; Putra, Muhammad Juliansyah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study aims to find out how the management of dynamic archives in universities has been run by the Universitas PGRI Palembang in order to realize a cyber university as well as the challenges and obstacles experienced in the management of dynamic archives. This research is a type of qualitative descriptive research and uses the analysis of the CIPP evaluation model. Informants in this study came from five archive managers. Data collection techniques used in-depth interviews, observation, and relevant literature studies. The data analysis technique includes four components, namely data collection, data condensation, data display and conclusion. The results of the study indicate that in archive management, PGRI University of Palembang has established an Archives Subdivision which is managed by the Library Unit. This has not been able to fulfill the archive management in each faculty. So that there are several challenges that must be carried out in archive management at Universitas PGRI Palembang, including designing an archive system with an archive retention schedule, shrinking archives, and maintaining archives. This study shows an overview of how archive management has never been studied before and can be used as a reference for other universities in South Sumatra that evaluating dynamic records management in each institution is important to do as early as possible.